ANALISIS PENGARUH PROMOSI E-COMMERCE DI YOUTUBE TERHADAP BRAND AWARENESS DAN DAMPAKNYA TERHADAP MINAT BELI - Angela Michelle Setiawan; Daru Purnomo; Pratiwi Cristin Harnita (Universitas Kristen Satya Wacana, 2021)
This study is different from other studies because there is an additional variable that becomes the limiting between the independent and dependent variables, namely the brand awareness variable, so the researcher wants to see whether the intervening variables in the study have an influence on the independent and dependent variables. The purpose of this research is to prove that there are other variables besides buying interest which can influence promotion. The theory used is Aidca's theory which is considered to be a reference in effective promotion. The data analysis technique uses path analysis. And based on the results, the indirect effect is greater than the direct effect, so that many variables outside of buying interest have an influence on promotion. Obtained the value of the indirect effect of 0.391 which is greater than the value of the direct effect of 0.275.